Pulmonary Histoplasmosis Mimicking Metastatic Lung Cancer: A Case Report - Ruegg, Gion (Diagnostics (Basel), 2021)
Histoplasmosis is a well-known endemic fungal infection but experience in non-endemic regions is often limited, which may lead to delayed diagnosis and extensive testing. The diagnosis can be especially challenging, typically when the disease first presents with pulmonary nodules accompanied by hilar and mediastinal lymphadenopathy, suggesting a much more common malignant disease. In this situation, a greater FDG uptake in draining lymph nodes in comparison with the associated lung nodule seen in [(18)F]FDG-PET/CT, the so-called “flip-flop fungus” sign, can help to orientate further diagnostic measures. We report a case of a 56-year-old woman living in Switzerland, a non-endemic region, whose diagnosis of imported histoplasmosis was delayed since the findings had been initially misinterpreted as pulmonary malignancy. Further, histological workup was inconclusive due to lack of specific fungal staining, leading to ineffective treatment and non-resolving disease. This paper intends to highlight the pitfalls in diagnosing Histoplasma capsulatum and presents images of particularities of fungal infections in [(18)F]FDG-PET/CT, which in our case showed a “flip-flop fungus” sign.